Ozone depletion in the high latitude lower stratosphere - 1979-1990 - Callis, Linwood B.; Boughner, Robert E.; Natarajan, Murali; Lambeth, James D.; Baker, Daniel N. (1991)
Archived Stratospheric Aerosol and Gas Experiment (SAGE, SAGE II) and Solar and Backscattered Ultraviolet (SBUV) data are used to examine lower stratospheric O3 variations at 50 deg latitude in both hemispheres. These data indicate that from 1979 to 1985, 73-90 percent of the total O3 changes have occurred below approximately 25 km in altitude. Significant O3 depletions (up to 15 percent) have occurred in the partial column (127-15.8 mbar) in both hemispheres with indications of a recovery after 1985. Two-dimensional model simulations of O3 changes from 1979 to 1990 have been carried out. Comparisons with O3 data are presented. Model results suggest that by 1985, significant declines in global O3 were caused by destruction by odd nitrogen associated with long-term variations in the flux of precipitating relativistic electrons (2.6 percent); solar UV flux changes (1.8 percent); the dilution effect associated with the Antarctic O3 hole (1.2 percent); and atmospheric increases in CH4, N2O, and chlorofluorocarbons (0.4 percent). Analyses of drift-corrected SBUV and Total Ozone Mapping Spectrometer data and model calculations indicate that between 1979 and 1985, reductions of 4.3 to 4.8 percent in total column O3 averaged between 65 deg S and 65 deg N have occurred. Calculations indicate a full global O3 decline of 5.2 percent (peak-to-peak) or 6 percent (annual average) between 1979 and 1985 with a partial recovery between 1985 and 1989.